"Multimacy": Performances of Intimacy on Facebook by Buenos Aires Adolescents. Issue 1 (5th December 2017) - Linne, Joaquín
Abstract: This article addresses the performances of intimacy displayed by adolescents of the City of Buenos Aires through the social networking site Facebook. The methodology used is mixed ethnography: on the one hand, conducting observations and thirty in‐depth interviews with adolescents from the study universe; on the other, analyzing personal photographs, given the centrality of this resource to the population at hand. In the results section, the performances which adolescents post on Facebook and comment on in the course of their everyday practices are described. The main contribution is the proposition of the concept of multimacy ("multimidad") to account for the ways in which they construct and share their intimacy through the platform.